Zina in Consensual Non-Monogamous Relationships: A Comparative Legal Analysis between Indonesian and Islamic Law - Fuadi Isnawan (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This article critically examines the emerging practice of swinger relationships in Indonesia, analyzing its legal implications under both Indonesian criminal law and Islamic criminal law. The primary objectives are to investigate the divergent regulatory frameworks concerning adultery in the context of consensual non-monogamous relationships within Indonesian criminal law and Islamic law, the sanctions prescribed by the Indonesian Criminal Code and Islamic ḥudud law; and the scope and nature of legal protections afforded to individuals engaged in swinger practices. Employing a qualitative research design with a phenomenological approach, this study analyzes primary sources such as the Indonesian Criminal Code (KUHP) and classical Islamic jurisprudence texts, alongside secondary sources comprising scholarly articles, legal commentaries, dissertations, and expert opinions. Data collection was conducted through a systematic literature review. The findings underscore fundamental distinctions between the secular orientation of Indonesian criminal law, which criminalizes adultery only when involving at least one legally married party and requires a formal complaint for prosecution, and the religiously anchored Islamic criminal law, which categorizes zina as a ḥudud offense with fixed divine penalties and stringent evidentiary standards. Legal protections under Indonesian law emphasize procedural safeguards and due process rights to prevent arbitrary prosecution, whereas Islamic law prioritizes the protection of individual honor (ḥifẓ al-‘irḍ) and social morality through rigorous evidentiary requirements and the prohibition of false accusations (qazf). Notably, Islamic legal provisions demonstrate substantive justice by exempting pregnant and nursing women from ḥudud punishments, reflecting considerations of humanity and equity. This research contributes novel insights into the complexities of harmonizing Indonesia’s secular criminal legal framework with its predominant religious values, particularly in addressing consensual non-monogamous sexual conduct such as swinger practices. It highlights the tension between evolving social behaviors and entrenched legal-religious norms, thereby informing ongoing debates on legal pluralism and human rights protections in Indonesian society.